Odpowiedzi

2010-01-18T19:23:56+01:00
B) x-4/2(w ułamku)+6-x/3(w ułamku)=2x-5/6(w ułamku) /*6
6*x-4/2(w ułamku)+6*6-x/3(w ułamku)=6*2x-5/6(w ułamku)
3x-12+12-2x=2x-5
3x-2x-2x=5
-x=5 /*(-1)
x=-5

c)x+4/5(w ułamku)+2x+9/10(w ułamku)=-2-x/2(w ułamku) /*10
10*x=4/5(w ułamku)+10*2x+9/10(w ułamku)=10*-2-x/2(w ułamku)
2x+8+2x+9=-10-5
2x+2x=-8-9-10-5
4x=-32 /:4
x=-8

d)2x-11/4 (w ułamku)+x+1/12(w ułamku)=x-1/6(w ułamku) /*12
12*2x-11/4 (w ułamku)+12*x+1/12(w ułamku)=12*x-1/6(w ułamku)
6x-3+x+1=2x-2
6x+x-2x=3-1-2
5x=0 /:5
x=0
1 5 1